Evidence for a Natural Deposition of Fish in the Middle Neolithic Site, Kainsbakke, East Jutland - Richter, Jane (Journal of Danish Archaeology, 1986)
Evidence for a Natural Deposition of Fish in the Middle Neolithic Site, Kainsbakke, East Jutland